2021
DOI: 10.1177/03331024211018137
|View full text |Cite
|
Sign up to set email alerts
|

CGRP-antibodies, topiramate and botulinum toxin type A in episodic and chronic migraine: A systematic review and meta-analysis

Abstract: Background The approval of monoclonal antibodies for prevention of migraine has revolutionized treatment for patients. Oral preventatives are still considered first line treatments as head-to-head trials comparing them with antibodies are lacking. Methods The main purpose of this study was to provide a comparative overview of the efficacy of three commonly prescribed migraine preventative medication classes. For this systematic review and meta-analysis, we searched the databases CENTRAL, EMBASE, and MEDLINE un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 58 publications
6
33
1
Order By: Relevance
“…Thus, the efficacy of a-tDCS of the left motor cortex seems to be comparable to topiramate used as first-line prophylactic treatment in CM. The efficacy of a-tDCS observed in the present study is also comparable to that recently reported in studies J o u r n a l P r e -p r o o f 12 considering the impact of botulinum toxin type A (BTA) or monoclonal antibodies against CGRP (mAbs) on the number of headache days as primary endpoint, reporting an effect size and responder rate of 50% [62,[66][67][68][69]. Thus, the efficacy of a-tDCS of the left motor cortex seems to be at least similar to all medications currently used as prophylactic treatment for CM and also for resistant CM, an observation that must to be confirmed by larger studies.…”
Section: Prophylactic Treatments Of CMsupporting
confidence: 89%
See 1 more Smart Citation
“…Thus, the efficacy of a-tDCS of the left motor cortex seems to be comparable to topiramate used as first-line prophylactic treatment in CM. The efficacy of a-tDCS observed in the present study is also comparable to that recently reported in studies J o u r n a l P r e -p r o o f 12 considering the impact of botulinum toxin type A (BTA) or monoclonal antibodies against CGRP (mAbs) on the number of headache days as primary endpoint, reporting an effect size and responder rate of 50% [62,[66][67][68][69]. Thus, the efficacy of a-tDCS of the left motor cortex seems to be at least similar to all medications currently used as prophylactic treatment for CM and also for resistant CM, an observation that must to be confirmed by larger studies.…”
Section: Prophylactic Treatments Of CMsupporting
confidence: 89%
“…The first-line prophylactic treatments of CM are based on medications [58][59][60][61][62]. The anticonvulsant topiramate has been recently recommended as the first-line prophylactic treatment for CM in French guidelines [59], because of the highest level of evidence of efficacy, notably based on a large, multicenter, controlled clinical trial [63].…”
Section: Prophylactic Treatments Of CMmentioning
confidence: 99%
“…Efficacy, expressed as the 50% response rate (reduction in monthly headache days) compared with placebo, is comparable between anti-CGRPs and BoNTA, while there are no major safety issues with both interventions. 44 Based on lower dropout rates, tolerability seems to be better with anti-CGRPs, 45 although one can argue that the application of BoNTA by a well-trained injector every three months might facilitate better compliance with BoNTA, compared with anti-CGRPs, which have to be self-injected by the patient typically every month, thus potentially being painful at the injection site as a result of their fast rate dispersion into the subcutaneous tissue. 46 In addition, there is evidence to support the beneficial effect of BoNTA injections at different sites, not just the forehead, in reducing the frequency and severity of comorbid psychiatric disorders, including depression and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…One reported both individual mAb reports vs. multiple onabotulinumtoxinA trials but also combined the outcomes of the mAb trials vs. the onabotulinumtoxinA trials ( 61 ). One other examined the three subcutaneous mAbs vs. topiramate and onabotulinumtoxinA in episodic and chronic migraine in a number needed to treat for a 50% responder rate (NNT50%) and likelihood to help or harm 50% rate (LHH50%) ( 62 ).…”
Section: Cgrp-receptor and Peptide Antibodiesmentioning
confidence: 99%